(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
A parabolic solar trough collector’s working fluid’s capacity for heat transmission was demonstrated to be greatly enhanced by turbulence (PTSC). This was accomplished by employing a novel approach that substituted a corrugated absorber tube for a plain one. The primary objective of the experiment was to boost the thermal efficiency of the PTSC system with the help of the corrugated absorber tube. Various tests were conducted, at different mass flow rates (m) ranging from 0.02 to 0.04 Kg/s. The Reynolds number (Re) was calculated to be between 2000 and 4000 for both plain and corrugated absorber tubes. The modification of the inner geometry of the PTSC system yielded remarkable outcomes, with a noticeable improvement in its thermal efficiency and heat transfer coefficient, thanks to the generation of flow vortices. While using a corrugated absorber tube instead of a plain tube, collection efficiency increased by 5.1% to 5.5% under the same operating circumstances.